2022
DOI: 10.1111/trf.17068
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell alloimmunization and other transfusion‐related complications in patients with transfusion‐dependent thalassemia: A multi‐center study in Thailand

Abstract: Background Thalassemia is a common genetic disease in Southeast Asia. Red blood cell (RBC) transfusion is an essential treatment for severe forms of thalassemia. We performed a study to demonstrate RBC alloimmunization and other transfusion‐related complications in patients with transfusion‐dependent thalassemia (TDT). Study Design and Methods A multi‐center web‐based registry of TDT was conducted in eight medical centers across Thailand. Thalassemia information, transfusion therapy, and transfusion‐related co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
2
2
Order By: Relevance
“…Unlike our study, Teawtrakul et al reported alloimmunization to be the most commonly documented transfusion‐related complication followed by allergic reactions among 421 transfusion‐dependent thalassemia patients in Thailand (15.6% and 13.0% for alloimmunization and allergic reactions, respectively) 24 . Seven patients included in their study had major transfusion‐related reactions ( n = 6 and 1 for anaphylaxis and TRALI, respectively) 24 . This difference observed in the frequency of major transfusion‐related reactions might be due to difference in the transfused RBC products.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Unlike our study, Teawtrakul et al reported alloimmunization to be the most commonly documented transfusion‐related complication followed by allergic reactions among 421 transfusion‐dependent thalassemia patients in Thailand (15.6% and 13.0% for alloimmunization and allergic reactions, respectively) 24 . Seven patients included in their study had major transfusion‐related reactions ( n = 6 and 1 for anaphylaxis and TRALI, respectively) 24 . This difference observed in the frequency of major transfusion‐related reactions might be due to difference in the transfused RBC products.…”
Section: Discussioncontrasting
confidence: 99%
“…Only one patient was reported to have anaphylaxis while none of the patients had TRALI. Unlike our study, Teawtrakul et al reported alloimmunization to be the most commonly documented transfusion‐related complication followed by allergic reactions among 421 transfusion‐dependent thalassemia patients in Thailand (15.6% and 13.0% for alloimmunization and allergic reactions, respectively) 24 . Seven patients included in their study had major transfusion‐related reactions ( n = 6 and 1 for anaphylaxis and TRALI, respectively) 24 .…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations